Bacterial Endotoxins: Biological Properties and Mechanisms - Salih, Aya Raad; Hameed, Noor Dheyaa (American Journal of Biology and Natural Sciences, 2025)
Gram-negative bacteria produce endotoxins (lipopolysaccharides, or LPS), which are pathogenic chemicals linked to the onset of Gram-negative shock. When endotoxins interact with the cells that are susceptible to lipopolysaccharides, they produce endogenous mediators such tumor necrosis factor alpha (TNFt). TNFt is the main mediator of the fatal impact of endotoxins, while macrophages are cells that mediate the hazardous actions of LPS. The several processes with endotoxin are bacterially sensitized would be covered in this review article.